2005
DOI: 10.1128/iai.73.3.1532-1542.2005
|View full text |Cite
|
Sign up to set email alerts
|

Antibody against V Antigen Prevents Yop-Dependent Growth ofYersinia pestis

Abstract: The V antigen (LcrV) of the plague bacterium Yersinia pestis is a potent protective antigen that is under development as a vaccine component for humans. LcrV is multifunctional. On the bacterial surface it mediates delivery of a set of toxins called Yops into host cells, and as a released protein it can cause production of the immunosuppressive cytokine interleukin-10 (IL-10) and can inhibit chemotaxis of polymorphonuclear neutrophils. It is not known how these mechanisms of LcrV operate, what their relative i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
56
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 54 publications
5
56
0
Order By: Relevance
“…For example, the Y. pestis secreted effector YopJ is a potent inhibitor of the NF-kB and MAPK signalling pathways (Sweet et al, 2007), and YopE has been shown to strongly inhibit activation of JNK, ERK and NF-kB with a coincident suppression of interleukin (IL)-8 production (Viboud & Bliska, 2005;Viboud et al, 2003). The Yersinia V-antigen has been reported to induce IL-10, which represses innate immunity (Brubaker, 2003;Overheim et al, 2005;Philipovskiy et al, 2005) but this activity has been challenged in more recent reports (Pouliot et al, 2007). Other mechanisms include the modification and/or loss of Toll-like receptor (TLR) ligands, denoted as pathogen-associated molecular pattern (PAMP) molecules (Kaufman et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Y. pestis secreted effector YopJ is a potent inhibitor of the NF-kB and MAPK signalling pathways (Sweet et al, 2007), and YopE has been shown to strongly inhibit activation of JNK, ERK and NF-kB with a coincident suppression of interleukin (IL)-8 production (Viboud & Bliska, 2005;Viboud et al, 2003). The Yersinia V-antigen has been reported to induce IL-10, which represses innate immunity (Brubaker, 2003;Overheim et al, 2005;Philipovskiy et al, 2005) but this activity has been challenged in more recent reports (Pouliot et al, 2007). Other mechanisms include the modification and/or loss of Toll-like receptor (TLR) ligands, denoted as pathogen-associated molecular pattern (PAMP) molecules (Kaufman et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The resistance is observed in multiple substrains of this line, and further studies by our laboratory have localized a major portion of the resistance phenotype to chromosome 1. This locus was initially discovered while looking into reports that interleukin-10 (IL-10) knockout mice were resistant to plague (15). We found that these mice possess a large portion of chromosome 1 from the 129 background and that it was this, in addition to the loss of the IL-10 allele, that contributed to improved survival (13).…”
mentioning
confidence: 97%
“…Opsonization with anti-LcrV antibodies increases the phagocytosis of Y. pestis by macrophages (10,29,43). The increased phagocytosis of Y. pestis mediated by anti-LcrV antibody opsonization is associated with reduced Yop translocation (10,29) and reduced apoptosis (10,29,43).…”
mentioning
confidence: 98%